2007
DOI: 10.2337/dc06-1138
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Soluble Transferrin Receptor According to Glucose Tolerance Status and Insulin Sensitivity

Abstract: OBJECTIVE -The relationships between iron metabolism and type 2 diabetes are bidirectional: iron affects glucose metabolism and glucose metabolism impinges on several iron metabolic pathways. The mechanisms of these interactions depend on poorly known factors. We aimed to study the contribution of the serum soluble transferrin receptor (sTfR). RESEARCH DESIGN AND METHODS -Circulating sTfR was evaluated in 221 men(97 with normal glucose tolerance [NGT], 36 with impaired glucose tolerance, and 88 with type 2 dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 21 publications
4
39
1
Order By: Relevance
“…Our data rule out any direct association of sTfR concentrations with indexes of insulin metabolism, obesity, and abnormal glucose tolerance, in sharp contrast with previous findings in older men in whom sTfR levels were higher in the subgroup presenting with altered glucose tolerance (28). Aside from the obvious sex differences in iron metabolism, the fact that the population studied here was older and that the diabetic patients were under pharmacologic treatment with several drugs, including insulin, sulfonylureas, and insulin sensitizers, may contribute to explain the discrepancies with our present data in much younger and untreated premenopausal women.…”
Section: Figurecontrasting
confidence: 85%
“…Our data rule out any direct association of sTfR concentrations with indexes of insulin metabolism, obesity, and abnormal glucose tolerance, in sharp contrast with previous findings in older men in whom sTfR levels were higher in the subgroup presenting with altered glucose tolerance (28). Aside from the obvious sex differences in iron metabolism, the fact that the population studied here was older and that the diabetic patients were under pharmacologic treatment with several drugs, including insulin, sulfonylureas, and insulin sensitizers, may contribute to explain the discrepancies with our present data in much younger and untreated premenopausal women.…”
Section: Figurecontrasting
confidence: 85%
“…6 We observed that the lower the insulin sensitivity, the higher the sTfR concentration. Furthermore, insulin sensitivity, independently of age, obesity and iron status, contributed independently to the variance of circulating sTfR concentration.…”
Section: Introductionmentioning
confidence: 55%
“…Furthermore, insulin sensitivity, independently of age, obesity and iron status, contributed independently to the variance of circulating sTfR concentration. 6 As insulin injection increases serum sTfR concentration in animal models, 7 hyperinsulinaemia may contribute to the inappropriately high sTfR concentration detected in individuals with altered glucose tolerance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies in general reported positive associations, although transferrin is inversely related to body iron stores and ferritin (8). In addition, while increased ferritin is quite consistently associated with hyperglycemia or insulin resistance, existing results on the soluble transferrin receptor (sTfR) and transferrin saturation (TSAT) are much more controversial (4,9,10,11,12,13).…”
Section: Introductionmentioning
confidence: 99%